Ukrainian adaptation of the Generalized Anxiety Disorder scale (GAD-7): diagnostic experience in the state of martial law - Aleksina , Nadiia; Gerasimenko , Olga; Lavrynenko , Denys; Savchenko , Olena (Insight: the psychological dimensions of society, 2024)
The aim of the research is to develop a Ukrainian-language adaptation of the GAD-7 generalized anxiety disorder assessment methodology and to test its psychometric properties. Methods. The forward and backward translation was carried out independently by several specialists with professional backgrounds in English philology and psychology, and then subjected to expert consistency checks. The data was collected online in two stages (December 2023, January 2024). The sample consisted of civilian Ukrainians aged 17–75 who lived in different regions of the country or were in forced migration abroad (786 and 315 people respectively), with a predominance of women with higher education. The results demonstrate the high psychometric competence of the adapted instrument. Excellent internal consistency and discriminant validity of the items were confirmed, as well as retest reliability, construct and criterion validity of the scale (correlations with the Adult Mental Health Questionnaire and the Positive Mental Health Scale). The factor structure of the methodology corresponds to the original univariate model. The GAD-7 indicator fairly accurately predicts the need to seek psychological help, has strong direct correlations with diagnostic variables measuring anxiety and depression, and negatively correlates with assessments of psychological health. At the same time, empirical indicators of the GAD-7 in the sample are distributed abnormally: more than 40.0% of respondents received a score of 10 or more points, which corresponds to the manifestation of pathological symptomatology. Such assessments are not recommended to be unequivocally interpreted as evidence of generalized anxiety disorder, as they may reflect a legitimate impact of prolonged military aggression on the psycho-emotional state of Ukrainians (maladaptive response to chronic stress, psychological trauma, etc.). Both statuses are indicative of mental health disorders and require appropriate interventions, but the ways and means of this care differ. The average anxiety score of women is significantly higher than that of men (9.70 and 6.93, respectively), which is consistent with the natural features of this condition. Conclusions. The adapted Ukrainian-language version of the GAD-7 is an effective tool for screening symptoms of anxiety disorder in psychological practice and scientific research, including in extreme living conditions. In a martial law situation, clinical disorders associated with anxiety should be distinguished from situationally conditioned reactions to objective danger, which requires additional research.
Keywords: anxiety, worry, pathological anxiety, mental health, screening, psychometric properties of the instrument.